Pengembangan Instrumen Perawatan Kaki untuk Pasien Diabetes dalam Upaya Pencegahan Terjadinya Luka Kaki Diabetes (LKD): Study Delphy - Eva Arna Abrar; Saldy Yusuf; Elly Lilianty Sjattar (Politeknik Kesehatan Kemenkes Mamuju, 2019)
Diabetes Mellitus (DM) is one of the chronic diseases that cause detrimental effects if left untreated. One of which is the occurrence of diabetic foot ulcer that may lead to amputation. Therefore, an effort is needed to avoid the aforementioned effects. One of the prevention acts is conducting foot care. In conducting foot care, a guide is needed as a reference. Therefore, this study aims to analyze the components of foot care that serve as a guide in performing foot care. Methode Classic Delphi and 3 Delphi online Rounds (Specific parts of Delphi study) are used in this study along with using 7 panelists from several cities in Indonesia. All panelist that consist of a person from Samarinda, a person from Medan, a person from Makassar, a person from Palu, a person from Tanjung Selor, and 2 people from Pontianak. They are qualified with Enterostomal therapy nurse (ETN) certification. Round 1 is started by using open question (Classic Delphi), round 2 and 3 using Online Delphi sent via WhatsApp application. Delphi 3 rounds produced 5 components which are: foot examination and pre-ulcer sign observation, foot washing, nail cutting, socks wearing and shoes checking (the inside and outside part) before and after use, can be used as a guide in foot care. Analysis of the foot care component through the Delphi study has resulted in a consensus that will be served as a reference for the implementation of foot care.